An Effective Strategy for Stabilizing Minimal Coiled Coil Mimetics - Wuo, Michael G. (J Am Chem Soc, 2015)
[Image: see text] Coiled coils are a major motif in proteins and orchestrate multimerization of various complexes important for biological processes. Inhibition of coiled coil-mediated interactions has significant biomedical potential. However, general approaches that afford short peptides with defined coiled coil conformation remain elusive. We evaluated several strategies to stabilize minimal helical bundles, with the dimer motif as the initial focus. A stable dimeric scaffold was realized in a synthetic sequence by replacing an interhelical ionic bond with a covalent bond. Application of this strategy to a more challenging native protein–protein interaction (PPI) suggested that an additional constraint, a disulfide bond at the internal a/d′ position along with a linker at the e/e′ position, is required for enhanced conformational stability. We anticipate the coiled coil stabilization methodology described herein to yield new classes of modulators for PPIs.